The Comparison of Inheritance Legal Position of Illegitimate Children Based on Islamic Law & Civil Law - Hanggartika, Edo Trisetya (TABELLIUS: Journal of Law, 2023)
The aim of this research is to analyze: 1) To determine the position of inheritance rights of illegitimate children based on the Compilation of Islamic Law and Civil Law. 2) To determine the similarities and differences in the legal position of inheritance of illegitimate children based on the Compilation of Islamic Law and Civil Law. The type of research used is normative legal research. The approach method used in this research is the statutory approach method and the legal comparison method. The research results concluded that the legal position of illegitimate children is based on Article 100 of the Compilation of Islamic Law. Children born out of wedlock only have a family relationship with their mother and her mother's family. In Article 186 of the Compilation of Islamic Law, children born outside of marriage only have an inheritance relationship with their mother and their mother's family. whereas in the Civil Code, a child born outside of a legal marriage has no civil relationship with his parents, unless there is a confession made by his biological parents. Keywords: Children; Compilation; Illegitimate Inheritance; Islamic.